Batu Pulut Village Population Management Information System using the Multi Attribute Utility Theory (MAUT) Method - Siregar, Diana Asmarani; Samsudin, Samsudin (Sistemasi: Jurnal Sistem Informasi, 2024)
Currently developing information technology can be used by village governments in order to increase the public reach of village governments for the community by providing easy access to information as well as developing better, transparent, effective and efficient village government activities. Currently, the population management information system in Batu Pulut village is still done manually or not many use media such as computers. The problems at the Batu Pulut Village Office are about work activities related to population service activities. The existing process is still in manual form, there is no system that is able to simplify the service process related to activities in the village and it still takes a long time so the process is often neglected. Another problem is in communities receiving aid where there is no system that is able to rank who the people are as recipients of village aid. The aim of this research is to create a population management information system for Batu Pulut Village using the Multi Attribute Utility Theory (MAUT) method. The method used in this system is the Multi Attribute Utility Theory method which is used as a method to assist this system in selecting communities as recipients of village assistance based on ranking data. The MAUT method aims to produce optimal decisions based on user assessments and references against a set of specified criteria. Based on the calculation results from the MAUT Method, a result of 0.75 was obtained with alternatives A2 and A4 as the best alternatives that were entitled to receive village assistance.